SINODALITAS GEREJA: STRATEGI MEWUJUDKAN UMAT KATOLIK YANG BERPARTISIPASI DI PAROKI SAKRAMEN MAHAKUDUS KISARAN - Alb Irawan Dwiatmaja (STP St. Bonaventura Medan, 2025)
This research aims to show strategies for realizing who participate in the Parish of Sakramen Mahakudus. The pastoral focus of the Archdiocese of Medan (KAM) in 2024 is Participation. Participation is fundamental and essential in building synodality. This paper will describe the strategy carried out by the Parish of Sakramen Mahakudus Kisaran to realize people who participate within the framework of the Church’s five pillars: kerygma, diakonia, koinonia, liturgia, martyria. This research was conducted using qualitative methods with a case study approach. The writer reads, analyzes and formulates writings related to the theme of the writing. The author is also directly involved in the process of identifying problems and formulating strategies for solving problems in accordance with the pastoral focus. The author collaborates with related parties jointly formulate a parish program based on pastoral focus.